2002
DOI: 10.2113/gsecongeo.97.5.971
|View full text |Cite
|
Sign up to set email alerts
|

Miocene Landscape Evolution and Geomorphologic Controls on Epithermal Processes in the El Indio-Pascua Au-Ag-Cu Belt, Chile and Argentina

Abstract: Ar-39 Ar geochronologic study of more than 90 igneous and alteration minerals from the district. These new ages, documented in detail by Bissig (2001) and Bissig et al. (2001), are derived from reliable plateaus representing more than 75 percent of the 39 Ar released. The data clarify some of the uncertainties arising from the earlier conventional K-Ar results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 40 publications
6
52
0
1
Order By: Relevance
“…3e; Mercer, 1983). In the latitudes of the study 508 area, glaciers are localized, inefficient erosion agents (Bissig et al, 2002), and thus an 509 unlikely cause for our observed low 10 Be concentrations, especially at foreland-S ca. 2 510…”
Section: Evidence In Favor Of a Tectonic Control Of Mass Fluxes 490mentioning
confidence: 93%
“…3e; Mercer, 1983). In the latitudes of the study 508 area, glaciers are localized, inefficient erosion agents (Bissig et al, 2002), and thus an 509 unlikely cause for our observed low 10 Be concentrations, especially at foreland-S ca. 2 510…”
Section: Evidence In Favor Of a Tectonic Control Of Mass Fluxes 490mentioning
confidence: 93%
“…Gregory-Wodziki (2000), based on various lines of evidence, concluded that the Altiplano of the central Andes had attained no more than half its modern elevation by 10.7 Ma, and that surface uplift of 2,300-3,400 m occurred since the Late Miocene. Bissig et al (2002) also recognized an important erosional surface in the high central Andes that formed in the interval 10-6 Ma.…”
Section: Depositional Environment and Tectonic Eventsmentioning
confidence: 99%
“…Estos pedimentos se agrupan en: la superficie Sierra Checos del Cobre, de probable edad oligocena; la superficie Asientos (>17,5 Ma) y el Pediplano de Atacama (15-10 Ma) (Bissig y Riquelme, 2009. En la región semiárida, entre los 29,5-30,5°S, tres superficies escalonadas de pedimentos fueron diferenciados en los interfluvios de la Cordillera Principal oriental, donde la presencia de niveles volcánicos -cubriendo cada uno de ellos-permitió diferenciarlos y datarlos en: Superficie Frontera-Deidad (17-15 Ma), Superficie Azufrera-Torta (14-12,5 Ma) y Superficie Los Ríos (10-6 Ma) (Bissig et al, 2002). Aguilar et al (2011) estimaron tasas de erosión media de entre 45 y 70 m/Ma para la incisión de la Superficie Los Ríos y formación de los actuales valles de la Cordillera Principal oriental de la región semiárida.…”
Section: Marco Geomorfológicounclassified